ME/CFS - the Severely and Very Severely Affected - Friedman, Kenneth; Bateman, Lucinda; De Meirleir, Kenny Leo (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Manuscripts in this monograph are sorted into five categories: 1. Case Reports: a description of living as a bedridden patient; structured interviews with severely affected ME/CFS patients; how past events contribute to severe ME/CFS; a comparison of moderately ill, severely ill, and very severely ill; case reports of ME/CFS in children. 2. A healthcare provider's view of managing ME/CFS patients. 3. Characterization of the Severely and Very Severely Affected: (1) the most troubling symptoms; (2) disease severity diminishes capacity for exercise, (3) operationalized definitions of the severely ill and very severely ill; (4) the usefulness of a modified Korean Chalder Fatigue Scale Questionnaire; (5) cardiac dimensions and function in patients; (6) an easier tilt test; and (7) review of sleep studies. 4. Progress in Diagnosis and Treatment: (1) objective measures for grading ME/CFS; (2) a sitting tilt test for orthostatic intolerance; (3) the benefits of IVIgG; (4) risks and protective factors in suicidality; (5) malnutrition and overcoming it; (7) partnerships between patients, caregivers, and providers, and the use of technology; (8) a holistic model of care, "Compassion in Practice; and (9) the effects of suffering, utilizing a four-phase model. 5. Impact of the Disease: (1) a historical perspective; (2) the impact of ME/CFS on psychosocial dynamics; (3) the educational needs of school-aged; and (4) the economic impact of ME/CFS